2019
DOI: 10.1002/ajpa.23920
|View full text |Cite
|
Sign up to set email alerts
|

Food abundance and weather influence habitat‐specific ranging patterns in forest‐ and savanna mosaic‐dwelling red‐tailed monkeys (Cercopithecus ascanius)

Abstract: Objectives: Primates that live in predominantly forested habitats and open, savanna mosaics should exhibit behavioral responses to differing food distributions and weather. We compared ecological constraints on red-tailed monkey ranging behavior in forest and savanna mosaic environments. Intraspecific variation in adaptations to these conditions may reflect similar pressures faced by hominins during the Plio-Pleistocene.Methods: We followed six groups in moist evergreen forest at Ngogo (Uganda) and one group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…The seasonal variation in activities and microhabitat use is thought to be related to thermoregulation in a number of primates (e.g., Alouatta palliate : Thompson, Williams, Glander, & Vinyard, 2016). For instance, when T a is high, primates reduce their daily travel distance (McLester, Brown, Stewart, & Piel, 2019), spend more time resting in the shade ( Callithrix jacchus : Abreu, De la Fuente, Schiel, & Souto, 2016; Fuente, Souto, Sampaio, & Schiel, 2014; Colobus polykomos : Dasilva, 1992; Papio cynocephalus: Stelzner, 1988), and stay in cooler microhabitats (e.g., caves) during the day ( Pan troglodytes verus : Pruetz, 2007; A. palliate : Thompson et al, 2016). On the other hand, when T a is low, primates respond by adopting alternative behaviors: They may change social relationships (increasing physical contact with others) within their group to benefit their thermal competences (McFarland et al, 2015), adjust nest architecture to increase thermoregulation (Stewart, Piel, Azkarate, & Pruetz, 2018), preferentially use heat‐conserving postures in sunny areas or stay under direct sunlight ( Alouatta caraya: Bicca‐Marques & Calegaro‐Marques, 1998; Callicebus nigrifrons: Gestich, Caselli, & Setz, 2014; P. cynocephalus: Stelzner & Hausfater, 1986), form huddles ( Macaca fuscata: Ogawa & Wada, 2011; Ueno & Nakamichi, 2018), select warmer microhabitats during the day ( A. palliate: Thompson et al, 2016), or remain for longer in caves ( P. hamadryas ursinus: Barrett, Gaynor, Rendall, Mitchell, & Henzi, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal variation in activities and microhabitat use is thought to be related to thermoregulation in a number of primates (e.g., Alouatta palliate : Thompson, Williams, Glander, & Vinyard, 2016). For instance, when T a is high, primates reduce their daily travel distance (McLester, Brown, Stewart, & Piel, 2019), spend more time resting in the shade ( Callithrix jacchus : Abreu, De la Fuente, Schiel, & Souto, 2016; Fuente, Souto, Sampaio, & Schiel, 2014; Colobus polykomos : Dasilva, 1992; Papio cynocephalus: Stelzner, 1988), and stay in cooler microhabitats (e.g., caves) during the day ( Pan troglodytes verus : Pruetz, 2007; A. palliate : Thompson et al, 2016). On the other hand, when T a is low, primates respond by adopting alternative behaviors: They may change social relationships (increasing physical contact with others) within their group to benefit their thermal competences (McFarland et al, 2015), adjust nest architecture to increase thermoregulation (Stewart, Piel, Azkarate, & Pruetz, 2018), preferentially use heat‐conserving postures in sunny areas or stay under direct sunlight ( Alouatta caraya: Bicca‐Marques & Calegaro‐Marques, 1998; Callicebus nigrifrons: Gestich, Caselli, & Setz, 2014; P. cynocephalus: Stelzner & Hausfater, 1986), form huddles ( Macaca fuscata: Ogawa & Wada, 2011; Ueno & Nakamichi, 2018), select warmer microhabitats during the day ( A. palliate: Thompson et al, 2016), or remain for longer in caves ( P. hamadryas ursinus: Barrett, Gaynor, Rendall, Mitchell, & Henzi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal variation in activities and microhabitat use is thought to be related to thermoregulation in a number of primates (e.g., Alouatta palliate: Thompson, Williams, Glander, & Vinyard, 2016). For instance, when T a is high, primates reduce their daily travel distance (McLester, Brown, Stewart, & Piel, 2019), spend more time resting in the shade (Callithrix jacchus: Abreu, De la Fuente, Schiel, & Souto, 2016;Fuente, Souto, Sampaio, & Schiel, 2014; Colobus polykomos: Dasilva, 1992; Papio cynocephalus : Stelzner, 1988), and stay in cooler microhabitats (e.g., caves) during the day (Pan troglodytes verus: Pruetz, 2007;A. palliate: Thompson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study site is characterized as a mosaic of miombo woodland, dominated by Brachystegia and Julbernardia spp., and small strips of riverine forest (Piel 2018). Mean annual rainfall since 2012 is ~1250mm, and daily mean temperatures in forest range from 10-33 o C throughout the year (McLester et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies have shown that chimpanzees frequently panthoot at food sources (Clark & Wrangham, 1993;Fedurek, Donnellan & Slocombe, 2014;Wrangham, 1977), call rate did not change with the proportion of time spent feeding in our study. However, our brief field season took place during the late dry season, when fruit availability is highest (McLester et al, 2019). The abundance of food might reduce competition among individuals and thus depress the need for calling.…”
Section: Travelling and Feeding Activitiesmentioning
confidence: 99%